Parental Communication Preferences in Rural Communities: A Qualitative Study on the Use of Indonesian Language in Parenting - Occe Luciana; Ria Kristia Fatmasari; Elfandri; Jamson Siallagan; Damon Wicaksi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
In the context of parenting, the choice of language by parents becomes a critical tool for conveying values, rules, and emotional support to children. This study investigates parental communication preferences for using Indonesian versus Madurese in rural communities and their impact on child-rearing practices. This research is a descriptive qualitative study. The method employed is the observation and participation technique, where the researcher observes and records the speech of rural communities related to parenting communication in Indonesian through recording and note-taking techniques. Besides, the researcher uses reflective introspective methods, based on the experiences of both the researcher and the informants. The researcher also conducts interviews with community leaders, linguists, artists, cultural figures, and rural community members. Once the data is collected, the researcher performs data reduction, classification, and validation according to the data type. Subsequently, data tabulation is carried out by coding each data entry listed in tables, followed by data interpretation and conclusion drawing. The research findings indicate a tendency among educated generations to raise their children using the Indonesian language, which is viewed negatively by Generation X. It is because the use of the Madurese language is considered an essential strategy in instilling moral values in children, especially in interactions with older individuals. The use of Indonesian is perceived as potentially distancing children from their cultural roots. Moreover, this study also finds that parental preferences for using the Indonesian language in parenting communication within rural communities encompass elements of nationalism, the role of Indonesian in rural societies, and Indonesian language communication in parenting in rural settings.